E-018 Transcirculation approach in complex endovascular procedures: a multicenter study. (22nd July 2019) - Roa, J; Dabus, G; Maud, A; Martinez-Galdamez, M; Paez-Granda, D; Kalousek, V; Mowla, A; Szeder, V; Jabbour, P; Ortega-Gutierrez, S; Hasan, D; Samaniego, E
Abstract : Background: Unfavorable anatomy can preclude traditional anterograde endovascular intervention through the parent vessel. Transcirculation approaches provide alternative pathways for successful treatment of these complex cases. Methods: Eight centers provided retrospective data on patients who underwent transcirculation procedures, including embolization of intracranial aneurysms (IAs), dural arteriovenous fistulas (dAVFs) and arteriovenous malformations (AVMs), and thrombectomy of acute ischemic strokes (AIS). Procedural complications, clinical and radiological outcomes were assessed after intervention and last available follow-up. Results: A total of 43 patients were treated using endovascular transcirculation approach: 24 IAs, 13 AIS, 3 AVMs and 3 dAVFs. Mean age was 56.9±15.3 years (range 18–82 years), and 24 (55.8%) were women. Most IAs (19/24, 79.2%) presented unruptured and were treated electively. 3 AVMs and 2 dAVFs presented ruptured. The most common indication for transcirculation approach was occlusion of the parent artery (21 patients, 48.8%). The posterior communicating artery (PCOM) was crossed in 20 (46.5%) cases (10 anterior-to-posterior, 10 posterior-to-anterior), anterior communicating artery (ACOM) in 17 cases, and vertebral artery (VA) in 2 cases. In four cases, combined approaches were used (3 ACOM right-to-left and viceversa, one double transcirculation ACOM/PCOM). The most common microcatheters used were Headway Duo (10 cases), SL-10 (6 cases), Marksmann (4 cases) and Echelon 10 (4 cases). In the AIS cases, 69.2% (9/13) achieved TICI 2b-3 recanalization. Ninety-six percent (23/24) of IAs achieved successful obliteration Raymond-Roy Occlusion Classification grades (RROC I-II). All AVMs and dAVFs achieved complete embolization. Two procedural complications were reported: one temporal arterial occlusion in a patient with IA, and one permanent arterial thrombosis in a patient with AIS. Of 21 IAs with radiological follow-up, complete angiographic obliteration (RROC I-II) was observed in 95.2% (20 cases). Conclusions: In this multicenter case series, the endovascular transcirculation approach was feasible and safe. Development of newer endovascular devices will further improve angiographic results and neurological outcomes in these complex cases. Disclosures: J. Roa: None. G. Dabus: None. A. Maud: None. M. Martinez-Galdamez: None. D. Paez-Granda: None. V. Kalousek: None. A. Mowla: None. V. Szeder: None. P. Jabbour: None. S. Ortega-Gutierrez: None. D. Hasan: None. E. Samaniego: None.